2019
DOI: 10.1016/j.neuron.2019.03.029
|View full text |Cite
|
Sign up to set email alerts
|

Glutamate-Releasing SWELL1 Channel in Astrocytes Modulates Synaptic Transmission and Promotes Brain Damage in Stroke

Abstract: Highlights d Swell1 is essential for the glutamate-permeable VRAC channel in astrocytes d Swell1 channel mediates both tonic and cell swelling-induced glutamate release d Astrocytic Swell1 regulates synaptic transmission and neuronal excitability d Knockout of astrocytic Swell1 provides neuroprotection from ischemic stroke

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

15
201
5
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 185 publications
(222 citation statements)
references
References 62 publications
15
201
5
1
Order By: Relevance
“…However, our brain-specific LRRC8A KO mice developed apparently normally and then died suddenly. Notably, our findings are in contrast with the study of Yang et al that produced the first conditional deletion of LRRC8A in the brain, using the relatively astrocyte-selective GFAP promoter (Yang et al 2019). In their publication, removal of astrocytic LRRC8A reduced neuronal excitability, impaired long-term potentiation and learning, and protected against experimental stroke; however, no increased mortality or developmental abnormalities in the CNS were reported (Yang et al 2019).…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…However, our brain-specific LRRC8A KO mice developed apparently normally and then died suddenly. Notably, our findings are in contrast with the study of Yang et al that produced the first conditional deletion of LRRC8A in the brain, using the relatively astrocyte-selective GFAP promoter (Yang et al 2019). In their publication, removal of astrocytic LRRC8A reduced neuronal excitability, impaired long-term potentiation and learning, and protected against experimental stroke; however, no increased mortality or developmental abnormalities in the CNS were reported (Yang et al 2019).…”
Section: Discussioncontrasting
confidence: 99%
“…Notably, our findings are in contrast with the study of Yang et al that produced the first conditional deletion of LRRC8A in the brain, using the relatively astrocyte-selective GFAP promoter (Yang et al 2019). In their publication, removal of astrocytic LRRC8A reduced neuronal excitability, impaired long-term potentiation and learning, and protected against experimental stroke; however, no increased mortality or developmental abnormalities in the CNS were reported (Yang et al 2019). These latter findings are consistent with the longstanding idea that astrocytic VRAC promotes neuronal excitability and brain damage via physiological and pathological release of the excitatory amino acid transmitters, aspartate and glutamate (Kimelberg and Mongin 1998;Kimelberg 2005;Mongin 2016;Mongin 2007).…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Such evidence supporting VRACs as astrocytic glutamate-releasing channels were indirect and based on pharmacological inhibitors, which may affect the function of other membrane proteins, including those directly involved in the glutamate transport (Bowens et al, 2013). Nevertheless, the latest work of Yang et al (2019) revealed astrocytic VRACs as major candidates mediating glutamate release in FCI. They took advantage of recent findings, which revealed that the leucine-rich repeat-containing protein 8A (LRRC8A, also named SWELL1) and its four other associated homologs (LRRC8B-E) form heteromeric VRACs (Voss et al, 2014;Schober et al, 2017;Osei-Owusu et al, 2018).…”
Section: Astrocytes Add Significantly To Glutamate Excitotoxicitymentioning
confidence: 99%
“…They took advantage of recent findings, which revealed that the leucine-rich repeat-containing protein 8A (LRRC8A, also named SWELL1) and its four other associated homologs (LRRC8B-E) form heteromeric VRACs (Voss et al, 2014;Schober et al, 2017;Osei-Owusu et al, 2018). In a well-designed approach, which employed a conditional knockout of Swell1 in astrocytes in an experimental model of stroke, Yang et al (2019) proved that the Swell1 -/mice had significantly smaller infarct volumes and better scores for overall neurological function than the control mice. In contrast to the role of VRACs in astrocytic glutamate release, their activation in neurons was shown to mediate Cl − influx and further contribute to cell damage by promoting neuronal swelling (Inoue and Okada, 2007;Zhang et al, 2011).…”
Section: Astrocytes Add Significantly To Glutamate Excitotoxicitymentioning
confidence: 99%